Pembuatan Alat Pencuci Kaki Otomatis Berbasis Mikrokontroler AtMega16 - Hanggoro Aji Al Kautsar; Sujiliani Heristian; Rachmat Adi Purnama; Agus Tri Purnomo; Ehon Abdulmanan (JURNAL TEKNIK KOMPUTER, 2019)
Prayer is an obligation that must not be abandoned except because of aging or obstruction that is justified by religious law, such as; women who have menstruation or postpartum. The person who leaves the prayer without a reason that is justified in the shari'ah of the law is an infidel. One of the conditions of prayer is in a holy and clean condition, but researchers can see the condition of a prayer house or mosque, the condition of the lower floor is dirty because many people pass by stepping on the floor of the lower terrace with the condition of using shoes. There is also a new one from the bathroom with no feet who then stepped on the floor. Stepping on a dirty floor will cause doubts. To cancel these doubts, it is better for researchers to maintain proper ablution conditions. Therefore, researchers made Automatic Foot Washers with Pear Sensors Based on Atmega Microcontroller 16. PIR (Pasive Infra Read) is one tool that can be used as a sensor to detect human presence which is then developed into an automatic footwashing device. And with the addition of an automatic door, the pilgrims will be orderly to wash their feet before entering the mosque. As well as the drying fan that the researcher added after the doorstop will make the pilgrim's feet dry immediately before stepping on the prayer area at the mosque.